Employment with a human face : balancing efficiency, equity, and voice - Budd, John W. (Cornell University Press, 2004)
"Budd proposes a fresh set of objectives for modern democracies - efficiency, equity, and voice - and supports this new triad with an intellectual framework for analyzing employment institutions and practices. In the process, he draws on scholarship from industrial relations, law, political science, moral philosophy, theology, psychology, sociology, and economics and advances debates over free markets, globalization, human rights, and ethics. He applies his framework to important employment-related topics, such as workplace governance, the New Deal industrial relations system, comparative industrial relations, labor union strategies, and globalization. These analyses create a foundation for reforming employment practices, social norms, and public policies. In the book's final chapter, Budd advocates the creation of the field of human resources and industrial relations and explores the wider implications of this renewed conceptualization of industrial relations."--Jacket